Transport Mechanisms for Human Fecal Indicator Bacteria in an Urban Stormwater Basin in Southeastern Wisconsin - (:unkn) unknown (My University, 2015)
Discharge of stormwater runoff to receiving waters is a known source of human pathogens; however the primary mechanisms by which these pathogens enter the stormwater system have yet to be quantified. This study builds upon and utilizes prior research findings in an attempt to explain the influence of the age of the pipes within stormwater and sanitary conveyance systems, rainfall and hydrogeological characteristics, and select infrastructure variables that contribute to the observed contamination of an urban stormwater basin in Southeastern Wisconsin. Over the course of approximately two years from 2012 to 2014, a total of 260 samples from 22 stormwater manholes and two terminal outfalls and 47 groundwater samples from three monitoring wells were collected and assessed by culture based methods, PCR and quantitative PCR (qPCR) to test for traditional and alternative indicators of fecal pollution within a 170-acre study area in the City of Wauwatosa, Wisconsin. Results indicated that all 22 manholes, both outfalls and each groundwater monitoring well location had the HF183 (human) Bacteroides genetic marker detected in at least one sample, suggesting sewage contamination is nearly ubiquitous within the 170-acre stormwater basin selected for this study. Although 90% of the study site manholes tested positively (i.e. >1,000 copy number (CN)/100 ml) in more than 50% of the samples collected, positive results from the monitoring wells were somewhat less consistent, as only 20% of all samples collected were identified as positive for human Bacteroides. Detection of human fecal indicator bacteria (FIB) correlated with age of pipe, seasonality, rainfall duration and volume, antecedent conditions and certain infrastructure conditions. The pervasive nature of human FIB within this study area suggests that the suspected presence of leaking laterals and multiple breaches within the sanitary sewer system’s structure are pathways for sanitary sewage contamination to enter the stormwater conveyance system.
Keywords: Fecal Indicators; Genetic Markers; Quantitative Polymerase Chain Reaction; Stormwater; Urban; Water Quality